PERBEDAAN PERSEPSI PASIEN TERHADAP KOMUNIKASI TERAPEUTIK ANTARA PERAWAT PEGAWAI TETAP DENGAN PERAWAT PEGAWAI KONTRAK DI RUANG DEWASA KELAS III RS. BAPTIS KEDIRI - Taviyanda, Dian (Jurnal Penelitian STIKES Kediri, 2010)
Background    : Perception of the patients to wards the official nurse to apprentice nurse is influenced by an environment factor namely therapeutic communication, it is done by  the nurse. The objective of this research  is to analyze the difference perception of the  patient to therapeutic communication between the official nurse and apprentice nurse in medical surgical ward of class III Baptis Hospital Kediri. Method            : This research was analytic comparation. The sample was all patients who taking care in medical surgical ward of class III who meet inclusion criterias. The number of the respondents were 58 using purposive sampling  technique. The research used single variable, that was perception of the patients to therapeutic communication. Conclusion      : The conclusion of this research that was no difference perception of the patients to the therapeutic communication between the job Holder nurse with the contract officer nurse in Adult Room of Class III in Baptis Hospital Kediri.